Экспериментальное изучение иерархии мотивов в зависимости от гендера студентов вузов [Articol] - Брайлян, Наталия (CEP USM, 2021)
Motivation for educational activity is a complicated complex that combines various educational processes, methods and pedagogical means of encouraging students to productive cognitive activity. Learning motivation directly contributes to the active assimilation of the content of education, that is, the knowledge, skills and abilities necessary for an individual. The process of the formation of motivation methods occurs in the course of the joint activities of teachers - this is the motivation for learning, and their attitude to professional duties, and on the other hand, for students, this is the motivation for learning and their internal, self-motivation. Learning process in the modern world, requires a number of important changes in the organization of teaching forms and methods of the educational process of students. There is also an urgent need to use new means and mechanisms of influence on the system of motivation of university students. It is also necessary to introduce new motivators for learning, taking into account gender differences, separately for boys and girls. The result of these activities is the construction of a complex of psychological and pedagogical impact on students, which will effectively increase the motivation for achieving success at the University.
EXPERIMENTAL STUDY OF THE HIERARCHY OF MOTIVES DEPENDING ON THE GENDER OF UNIVERSITY STUDENTS
Keywords: learning activities; motivation; needs; motivation for success; gender